Feasibility Study of a Compatible Design Method for Asphalt Concrete-Based Track Substructure Considering Viscoelastic Properties. Issue 5 (May 2023) - Hu, Ting; Fang, Mingjing; Fang, Kun; Mo, Liantong; Xiao, Yue
An evaluation is needed as to whether the constant thickness for the formation layer of 0.4 m and the bottom layer of 2.3 m in China's current subgrade design is appropriate for the asphalt trackbed given its viscoelastic properties. This paper presents numerical research on the compatible design of roadbed thickness for asphalt concrete-based track (AC-based track) with SBS-25, using finite element modeling (FEM). Accordingly, a compatible design method for the substructure of an AC-based track was proposed following field and data investigation, material and numerical testing, as well as optimization and field testing with soundness verification. Compared with the traditional design, the formation layer needs to be strengthened, and the bottom layer thickness can be appropriately reduced or replaced with building solid waste. The dynamic stress attenuation rate and dynamic-static stress ratio are taken as the design standards of formation and bottom layers, respectively. The optimal design scheme at 20°C is determined when the asphalt track is 300 mm thick, the formation layer of 0.50 m and the bottom layer of 1.87 m are matched. However, at 40°C, the dynamic deformation control fails to pass the verification. Therefore, it is necessary to adjust the thickness of the asphalt trackbed or change the types of asphalt binder to carry out the numerical test again if applied in a high-temperature region. The findings contribute to the AC-based track substructure design; however, the proposed design method still needs further improvement and verification from the field or full-scale indoor tests.